Preparation and application of ionic vinyl metal covalent organic framework material

By introducing metal and ion sites in situ, the synthesis process of functionalized COFs is simplified, the existing COFs stability and cumbersome synthesis problems are solved, and efficient CO2 cycloaddition reaction and catalytic performance improvement is achieved.

CN119463084AActive Publication Date: 2025-02-18LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411612630.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The multi-step synthesis of existing functionalized covalent organic frame materials (COFs) is relatively cumbersome, and the COFs of imine bond links are poor, making it difficult to achieve efficient CO2 cycloaddition reactions.

Method used

The Knoevenagel condensation reaction introduces metal and ionic sites in situ, and prepares a highly crystalline carbon-carbon double-bond ionic metal covalent organic framework material, and uses solvothermal and methyl to condense the aldehyde group and methyl group to form Stable framework structure.

Benefits of technology

The uniform distribution of functional sites is achieved, the stability and catalytic performance of the material are improved, the synthesis process is simplified, and the efficiency of CO2 cycloaddition reaction is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463084A_ABST
    Figure CN119463084A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of an ionic vinyl metal covalent organic framework material, and belongs to the technical field of organic synthesis. The preparation method comprises the following steps: adding a metal cluster containing an aldehyde group and an ionic monomer containing a methyl group into a reaction tube, and reacting in an organic solvent under the catalytic action of piperidine to generate the crystalline ionic carbon-carbon bond linked metal covalent organic framework material. The sp2c-COFs are generated by utilizing a Knoevenagel condensation reaction through a bottom-to-top strategy, the stability of the material is improved through carbon-carbon bond linkage, and metal and ion sites are uniformly distributed in the framework material according to the method. In the material, metal and ions are introduced into a monomer through in-situ synthesis, so that uniform distribution of functional sites is realized, the problems of non-uniform metal distribution, difficulty in quantification and the like caused by introduction of metal through a post-modification method at present are solved, and the material has important value in performance improvement of COFs (Covalent Organic Frameworks) materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of porous organic materials, and relates to a covalent coordination polymer material, and in particular to a preparation method and application of a vinyl-linked ionic metal covalent organic framework material. Background Art

[0002] Covalent organic frameworks (COFs) are a type of crystalline porous material prepared by reversible condensation reactions of organic "building blocks" composed of lightweight elements such as C, H, O, N, and B. The organic building blocks are integrated into primary or advanced structures with a clear structure. The development of COFs provides ideas for designing periodically ordered polymer materials. The chain grows in a two-dimensional or three-dimensional structure by step-growth polymerization. Therefore, the rigid skeleton of COFs is long-range ordered under its topological structure. As an emerging class of organic porous materials, the library of COFs has expanded rapidly under the interest of researchers since 2005. Subsequently, boron-oxygen bonds, hydrazone bonds, enone bonds, imide bonds, and imine bonds formed by reversible condensation reactions were reported. It has developed to the less reversible and more stable triazine bonds and vinyl-linked carbon-carbon double bonds. COFs not only have the characteristics of low density and high specific surface area of ​​conventional porous materials, but also have unique advantages given by their organic crystalline structure: compared with inorganic porous materials such as zeolites and molecular sieves, COFs have the advantages of variable topological structure, adjustable nanopore size and easy functionalization; compared with MOFs, COFs have higher chemical stability in aqueous solution, even in strong acid and strong base solutions. In addition, compared with amorphous porous organic materials such as conjugated microporous polymers (CMPs), crystalline COFs have a regular, ordered and uniform pore structure. COFs are mainly functionalized by post-modification methods, such as loading metals and ionic liquids to form composite materials with MOFs. Thanks to the above advantages, COFs have been widely used in gas adsorption, heterogeneous catalysis, energy storage and conversion, sensing and other fields in recent years.

[0003] Vinyl-linked COFs (sp 2 Since its first report in 2016, sp-COFs have attracted widespread attention from researchers due to their poor bonding reversibility, acid-base stability, and strong conjugation. Currently, sp-COFs with vinyl linkages are mainly prepared through Knoevenagel condensation, Aldol condensation, and HWE reaction. 2 However, the types of monomers involving carbon-carbon double bonds are limited and the synthesis of monomers is relatively complicated. 2 There are few reports on c-COFs. Therefore, it is necessary to synthesize simple and readily available novel aldehyde and methyl monomers to prepare sp 2 c-COFs are necessary.

[0004] In recent years, covalent organic frameworks have been widely used in CO due to their high specific surface area and modifiable functionalization. 2 The advantages of cycloaddition reactions are becoming increasingly prominent. The introduction of Lewis acid and nucleophilic ion sites into the COFs framework can synergistically catalyze CO 2 Cycloaddition reaction. Most of the COFs reported so far for catalyzing this reaction are connected by imine bonds. The functional groups are introduced into the COFs framework through a multi-step post-modification method. The steps are relatively cumbersome, and the amount of functional groups introduced by this method cannot be accurately determined. Therefore, it is necessary to develop new methods to synthesize functionalized COFs with high stability. Summary of the invention

[0005] In order to solve the problem that the current multi-step synthesis of functionalized COFs is relatively cumbersome and the stability of COFs linked by imine bonds is poor, the present invention discloses a method for preparing functionalized ionic vinyl metal covalent organic framework materials, and metal and ion sites are introduced in situ on aldehyde monomers and methyl monomers. Through the Knoevenagel condensation reaction, a certain catalyst is added by a solvothermal method to make the aldehyde group and the methyl group undergo a Knoevenagel condensation reaction. The metal center as the active site can catalyze a variety of reactions, and the introduction of ion sites can improve the microenvironment of the material pores, greatly improving the catalytic performance of COFs.

[0006] The ionic vinyl metal covalent organic framework material of the present invention has a structure shown in the following formula (I) or (II): The preparation method is as follows: a cyclotrinuclear copper metal cluster containing an aldehyde group and an ionic monomer containing a methyl group are co-dissolved in an organic solvent, heated to 170-190° C. under the catalysis of piperidine for reaction for 72-96 hours under vacuum conditions, then cooled to room temperature, centrifuged, washed, and vacuum dried to obtain the ionic vinyl metal covalent organic framework material.

[0007] The reaction route is as follows: .

[0008] The cyclotrinuclear copper metal cluster containing an aldehyde group is C 12 H 9 Cu 3 N 6 O 3 (Cu 3 L 3 The methyl-containing ionic monomer is 1,2,4,6-tetramethylpyridinium iodide (TMPI-I) or 1,2,4,6-tetramethylpyridinium-1-ammonium tetrafluoroborate (TMPI-BF 4);The molar ratio of the cyclotrinuclear copper metal cluster containing aldehyde group to the ionic monomer containing methyl group is 1:4~4:1. The organic solvent is N,N-dimethylformamide (DMF), o-dichlorobenzene ( o -DCB) or mesitylene (mes).

[0009] The 1,2,4,6-tetramethylpyridine iodide is prepared by dissolving 2,4,6-trimethylpyridine and methyl iodide in dichloromethane, stirring and reacting for 20 to 25 hours at room temperature, filtering, washing and drying; wherein the molar ratio of 2,4,6-trimethylpyridine to methyl iodide is 1:3 to 3:1.

[0010] The 1,2,4,6-tetramethylpyridine-1-tetrafluoroboric acid is prepared by using 2,4,6-trimethylpyridine and tetrafluoroboric acid as raw materials, maintaining the temperature at 140-160°C and 80-120W microwave power for 10-20 minutes under the action of trimethyl orthoformate, a methylating agent, cooling to room temperature, filtering, washing, and drying. The molar ratio of 2,4,6-trimethylpyridine to tetrafluoroboric acid is 1:2-2:1, and the molar ratio of tetrafluoroboric acid to trimethyl orthoformate is 1:3-3:1.

[0011] Compared with the prior art, the preparation method of the ionic vinyl metal covalent organic framework material of the present invention is to prepare an ionic metal covalent organic framework material with high crystallinity carbon-carbon double bond linkage by condensing pyrazolyl metal clusters with pyridine methyl organic monomers. 2 c-COFs, carbon-carbon bond linkage improves the stability of the material, and the method evenly distributes the metal and ion sites in the framework material. In this material, metals and ions are introduced into the monomer by in-situ synthesis, achieving uniform distribution of functional sites, solving the problems of uneven metal distribution and difficulty in quantification caused by the current introduction of metals by post-modification methods, and having important value for improving the performance of COFs materials. The ionic vinyl metal covalent organic framework material prepared by the method of the present invention has the advantages of high specific surface area and high stability, and can be used in catalysis, adsorption sensing and other fields. At the same time, the ionic metal covalent organic framework prepared by the method of the present invention also has excellent CO 2 Cycloaddition reaction performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is the XRD refinement pattern of the ionic vinyl metal covalent organic framework material prepared in Example 1.

[0013] Figure 2 This is the XRD refinement pattern of the ionic vinyl metal covalent organic framework material prepared in Example 2.

[0014] Figure 3 N is the ionic vinyl metal covalent organic framework material prepared in Example 1 2 Physical adsorption graph (a) and pore size distribution graph (b).

[0015] Figure 4 The CO of the ionic vinyl metal covalent organic framework material prepared in Example 1 2 Physical adsorption diagram.

[0016] Figure 5 The CO of the ionic vinyl metal covalent organic framework material prepared in Example 1 2 Schematic diagram of the cycloaddition cycle performance.

[0017] Figure 6 The CO of the ionic vinyl metal covalent organic framework material prepared in Example 1 2 Cycloaddition substrate universality diagram. DETAILED DESCRIPTION

[0018] The present invention is further explained below with reference to specific embodiments.

[0019] Embodiment 1: (1) Cu 3 L 3 Preparation Weigh 200 mg of copper nitrate trihydrate (0.83 mmol) and 96 mg of 1H-pyrazole-4-carboxaldehyde (1.0 mmol) into a 25 mL sample bottle, add 6.7 mL of N,N-dimethylformamide (DMF), 5 mL of H 2 O and 6.7 mL of ethanol. The bottle was sealed and placed in an oven at 100 °C for 12 h. After the reaction, pale yellow needle-shaped crystals were obtained. The solid was filtered and soaked in water for 3 days, during which the water was changed every 8 h. Finally, the crystals were washed three times with acetone (30 mL×3) and dried in vacuum at 120 °C for 24 h, with a yield of 65%.

[0020] (2) Preparation of TMPI-I Dissolve 2,4,6-trimethylpyridine (2 mL, 15 mmol) and iodomethane (2.85 mL, 45 mmol) in 10 mL of CH 2 Cl 2 The mixture was stirred at room temperature overnight and filtered to obtain a white solid, which was then recrystallized from methanol and filtered to obtain the target product, which was then dried under vacuum at 60 °C for 6 h.

[0021] (3) Preparation of ionic vinyl covalent organic framework material TMPI-Cu-MCOF-I Weigh Cu 3 L3 (23.9 mg, 0.05 mmol) and TMPI-I (13.2 mg, 0.05 mmol) were placed in a reaction tube, and 2 mL of DMF and o -DCB (volume ratio 3:1), 100 μL piperidine was added as a catalyst, ultrasonicated for 5 min, and then the reaction tube was frozen in liquid nitrogen environment. 2 After three cycles of vacuuming, the reaction tube was sealed and heated at 180 °C for 4 days. After the reaction was completed, it was cooled to room temperature and replaced with DMF, methanol and CH 2 Cl 2 Wash 2 to 3 times to remove the oligomers or monomers in the system, then dry the product in a vacuum drying oven at 100 °C for 12 h, and collect the solid by filtration to obtain a reddish-brown metal cluster-based crystalline porous material TMPI-Cu-MCOF-I. The structural formula of the material is: .

[0022] The yield of the above material is 91%. The obtained ionic vinyl metal covalent organic framework material is subjected to powder X-ray diffraction, and its XRD refinement pattern is as follows: Figure 1 As shown, it can be seen that the material has good crystallinity. Through structural simulation by MaterialsStudio, it can be concluded that the structure is an AA stacking model.

[0023] Example 2 (1) Cu 3 L 3 Preparation Same as Example 1.

[0024] (2) TMPI-BF 4 Preparation In an ice-water bath, 2,4,6-trimethylpyridine (2.5 mmol) and tetrafluoroboric acid (2.5 mmol) were mixed, and then the temperature was raised to room temperature and maintained for 1 h. After the reaction was completed, the obtained mixture was evaporated to dryness under reduced pressure and dried in vacuo. Trimethyl orthoformate (7.5 mmol) was added to the solid obtained above, and the mixture was kept in a microwave reactor (150 °C, 100 W) for 10 min. After cooling to room temperature, the obtained solid was filtered, washed with ethanol, and vacuum dried to obtain the product (TMPI-BF 4 ).

[0025] (3) Ionic vinyl covalent organic framework material TMPI-Cu-MCOF-BF 4 Preparation Weigh Cu 3 L 3(23.9 mg, 0.05 mmol) and 9.2 mg (0.05 mmol) TMPI-BF 4 In the reaction tube, 2 mL of DMF and mes (volume ratio 3:1) were added, followed by piperidine as a catalyst, and ultrasonication was performed for 5 min. The reaction tube was frozen in liquid nitrogen and passed through N 2 After three cycles of vacuuming, the reaction tube was sealed and heated at 180 °C for 4 days. After the reaction was completed, it was cooled to room temperature and washed with DMF, methanol, dichloromethane and ethanol 2 to 3 times in sequence to remove the oligomers or monomers in the system. The product was then placed in a vacuum drying oven at 100 °C and dried for 12 h. The solid was collected by filtration to obtain a wine-red ionic vinyl metal covalent organic framework material TMPI-Cu-MCOF-BF 4 , the structural formula of the material is: .

[0026] The prepared ionic vinyl metal covalent organic framework material was subjected to powder X-ray diffraction, and its XRD refinement pattern is shown as follows: Figure 2 As shown, it can be seen that the material has good crystallinity. Through structural simulation with Materials Studio, it can be concluded that the structure is an AA stacking model.

[0027] Product performance evaluation and application research In order to reasonably characterize the porosity of the ionic vinyl metal covalent organic framework material structure, the material was degassed at 120°C for 12 h and then tested for nitrogen adsorption at 77 K.

[0028] Figure 3 a is N of the ionic vinyl metal covalent organic framework material prepared in Example 1 2 Physical adsorption and desorption isotherms, Figure 3 b is the pore size distribution curve of Example 1, from which it can be seen that the specific surface area of ​​the material is 361 m 2 / g, and the pore size distribution is 1.2 nm, indicating that the material has a microporous skeleton structure.

[0029] Figure 4 The CO of the ionic vinyl metal covalent organic framework material prepared in Example 1 2 Physical adsorption diagram. Figure 4 It can be seen that the material prepared in Example 1 has a CO 2 The adsorption capacity of CO was 1.95 mmol / g at 298K. 2 The adsorption capacity is 1.4 mmol / g, indicating that the material prepared in Example 1 can effectively adsorb CO 2 , can be used as CO 2Cycloaddition reaction catalyst.

[0030] CO of ionic vinyl metal covalent organic frameworks 2 Cycloaddition performance test The ionic vinyl metal covalent organic framework material prepared in Example 1 was dried at 120°C under vacuum for 12 hours. Then different equivalents (1mmol%, 2mmol%, 3mmol%, 4mmol%, 5mmol%, 6mmol%, 7mmol%, 8mmol%, 9mmol%, 10mmol%, 11mmol%) of the dried material were put into a reactor as a catalyst, 10mmol of epichlorohydrin was added, and CO 2 The gas was replaced three times to exhaust the air in the reactor and finally filled with 2MPa CO 2 , 120℃ for 48h, and then the reaction was investigated with the reaction time, reaction temperature and CO 2 At the same time, the same equivalent of the ionic vinyl metal covalent organic framework material prepared in Example 2 was dried at 120°C under vacuum for 12 hours, and then put into a reactor as a catalyst, 10 mmol of epichlorohydrin was added as a reactant, and a certain pressure of CO was charged into the reactor. 2 , exhaust the air in the reactor, and after three cycles of this operation, introduce 2MPa CO 2 The reaction was carried out at 120 °C for 48 h. After the reaction was completed and the temperature was cooled to room temperature, a deuterated reagent and an internal standard were added. 1 The yield of the product was tested by H NMR. It can be seen that 95% of the cyclic carbonate yield was obtained by using TMPI-Cu-MCOF-I as the catalyst, while the comparative sample TMPI-Cu-MCOF-BF 4 The yield of the cyclic carbonate was lower (78%), presumably due to the stronger nucleophilic reactivity of the iodide ion. The data are listed in Table 1.

[0031] Table 1 CO of ionic vinyl metal covalent organic framework materials prepared in Example 1 and Example 2 2 Cycloaddition performance .

[0032] CO of ionic vinyl metal covalent organic frameworks 2 Cycloaddition reaction catalytic cycle test The ionic vinyl metal covalent organic framework material prepared in Example 1 was dried under vacuum at 120°C for 12 h, and then 8 mmol% of the dried material was placed in a reaction kettle, 10 mmol of epichlorohydrin was added, and a certain pressure of CO was charged into the kettle. 2 , exhaust the air in the reactor, repeat the operation three times, and finally fill it with 2MPa CO 2, 120℃ for 48h. After the reaction is completed and the temperature is restored to room temperature, cool it in an ice water bath and slowly open the exhaust valve to release the remaining CO 2 Open the reactor, add internal standard 1,1,2,2-tetrachloroethane, and use a small amount of CDCl 3 -d 6 Clean the inner wall of the reactor, collect the washing liquid into the reactor, perform ultrasonication until the generated reaction stock solution is completely dispersed, centrifuge to separate the catalyst, take 0.5 mL of the supernatant and add it to the NMR tube, and use NMR hydrogen spectroscopy ( 1 H NMR) quantitative analysis and calculation of yield. The catalyst was DMF, CH 3 OH and CH 3 CH 2 OH, and further purified by Soxhlet extraction, and then dried at 120 °C in vacuum for next use. The performance of the catalyst after 6 cycles is as follows: Figure 5 As shown, the yield of cyclic carbonate did not decrease significantly, indicating that the material prepared in Example 1 has good cycle stability.

[0033] CO of ionic vinyl metal covalent organic frameworks 2 Study on the universality of cycloaddition substrates After obtaining the optimal reaction conditions using epichlorohydrin as a model reaction, the substrate applicability of the material prepared in Example 1 was further explored by trying to convert CO 2 Cycloaddition reactions with several epoxides are carried out to prepare a variety of cyclic carbonates. Figure 6 As shown, 1a-1f represent epoxy compounds with different substituents, which are epichlorohydrin, epibromohydrin, 4-((allyloxy)methyl)-1,3-dioxolane-2-one, 4-(butyloxymethyl)-1,3-dioxolane-2-one, 1,4-butanediol diglycidyl ether and styrene oxide, and 2a-2f represent the corresponding cyclic carbonate products. The ionic vinyl metal covalent organic framework material prepared in Example 1 was dried at 120°C under vacuum for 12 hours, and then 8 mmol% of the above activated material was taken as a catalyst and placed in a reaction kettle, 10 mmol of epichlorohydrin was added, and a certain pressure of CO was charged into the kettle. 2 , exhaust the air in the reactor, repeat this operation three times, and finally fill it with 2MPa CO 2 , 120℃ for 48h. After the reaction is completed and the temperature is restored to room temperature, cool it in an ice water bath and slowly open the exhaust valve to release the remaining CO 2 Open the reactor, add internal standard 1,1,2,2-tetrachloroethane, and use a small amount of CDCl 3 -d 6Clean the inner wall of the reactor, collect the washing liquid into the reactor, perform ultrasonication until the generated reaction stock solution is completely dispersed, centrifuge to separate the catalyst, take 0.5 mL of the supernatant and add it to the NMR tube, and use NMR hydrogen spectroscopy ( 1 H NMR) quantitative analysis and yield calculation. The results showed that 1a-1e reacted with CO without adding additives. 2 Surprisingly, 1,4-butanediol diglycidyl ether and CO 2 The cycloaddition reaction gave a product yield of 89%, indicating that the material prepared in Example 1 has good substrate universality. Since the molecular size of styrene oxide (1f) (reaction time: 72 hours) is relatively large, it is not conducive to substrate adsorption and product conversion and desorption at the active center of the catalyst, so the reaction activity is relatively poor. It is speculated that the poor nucleophilic reaction activity of β-carbon may also be the reason for the low yield.

Claims

1. An ionic vinyl metal covalent organic framework material, characterized in that: It has the structure shown below: , Wherein, the dotted line represents the connection position of the bond; R is selected from any of the following structures: or .

2. A method for preparing the ionic vinyl metal covalent organic framework material as claimed in claim 1, characterized in that: The cyclotrinuclear copper metal cluster containing aldehyde groups and the ionic monomer containing methyl groups are dissolved in an organic solvent, and the temperature is raised to 170-190° C. under the catalysis of piperidine for reaction for 72-96 hours under vacuum conditions, and then cooled to room temperature, centrifuged, washed, and vacuum dried to obtain the ionic vinyl metal covalent organic framework material.

3. A method for preparing an ionic vinyl metal covalent organic framework material as claimed in claim 2, characterized in that: The cyclotrinuclear copper metal cluster containing an aldehyde group is C 12 H9Cu3N6O3; the ionic monomer containing a methyl group is one of 1,2,4,6-tetramethylpyridinium iodide or 1,2,4,6-tetramethylpyridinium-1-ammonium tetrafluoroborate; the molar ratio of the cyclotrinuclear copper metal cluster containing an aldehyde group to the ionic monomer containing a methyl group is 1:4~4:

1.

4. A method for preparing an ionic vinyl metal covalent organic framework material as claimed in claim 3, characterized in that: The 1,2,4,6-tetramethylpyridine iodide is prepared by dissolving 2,4,6-trimethylpyridine and iodomethane in dichloromethane, stirring and reacting at room temperature for 20-25 hours, filtering, washing and drying; the 1,2,4,6-tetramethylpyridine-1-tetrafluoroboric acid is prepared by using 2,4,6-trimethylpyridine and tetrafluoroboric acid as raw materials, maintaining the temperature at 140-160° C. and 80-120 W microwave power for 10-20 minutes under the action of methylating agent trimethyl orthoformate, cooling to room temperature, filtering, washing and drying.

5. A method for preparing an ionic vinyl metal covalent organic framework material as claimed in claim 4, characterized in that: The molar ratio of the 2,4,6-trimethylpyridine to methyl iodide is 1:3-3:1; the molar ratio of the 2,4,6-trimethylpyridine to tetrafluoroboric acid is 1:2-2:1, and the molar ratio of tetrafluoroboric acid to trimethyl orthoformate is 1:3-3:

1.

6. The method for preparing the ionic vinyl metal covalent organic framework material according to claim 2, characterized in that: The organic solvent is N,N-dimethylformamide (DMF), o-dichlorobenzene ( o -DCB) or mesitylene (mes).

7. Use of the ionic vinyl metal covalent organic framework material as claimed in claim 1 in a CO2 cycloaddition reaction.

Citation Information

Patent Citations

  • Carbon-carbon double bond bridging covalent organic framework material and preparation method thereof

    CN112708090A

  • Preparation method of metal cluster-based crystalline porous material

    CN113717397A

  • Bifunctional catalyst based on covalent organic framework material as well as preparation method and application of bifunctional catalyst

    CN115608421A

  • Ionic covalent organic framework material as well as solid-phase synthesis method and application thereof

    CN117624521A

Cited By

  • Metal covalent organic framework Cu3-PA-MCOF photocatalyst and application thereof in thioamide derivative synthesis

    CN121293527A